2021
DOI: 10.1002/jum.15828
|View full text |Cite
|
Sign up to set email alerts
|

The Visualized Urethral Mobility Profile in Stress Urinary Incontinence Described by Four‐Dimensional Transperineal Ultrasound

Abstract: Objectives-To describe the urethral mobility during urine leaking in stress urinary incontinence (SUI) by transperineal ultrasound (TPUS) with urethral mobility profile (UMP) analysis.Methods-This was a prospective study of 380 women who had a cough stress test (CST) with TPUS. UMP software automatically placed six equidistant points from the bladder neck (Point 1) to the external urethral meatus (Point 6) and determined their x and y coordinates relative to the symphysis pubis. Urethral mobility vector of Poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
(63 reference statements)
1
4
0
Order By: Relevance
“…3). 15 This helps to validate the results of the previous study and further supports that more urethral mobility that consists of the urethra swinging around the pubic bone toward the outside of the body is associated with SUI 12,15,21 …”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…3). 15 This helps to validate the results of the previous study and further supports that more urethral mobility that consists of the urethra swinging around the pubic bone toward the outside of the body is associated with SUI 12,15,21 …”
Section: Discussionsupporting
confidence: 75%
“…Other studies have analyzed urethral shape using ultrasound 12,21 . Pirpiris et al 12 found that SUI was strongly associated with mobility of the midurethra in translabial ultrasound and Zhao et al 21,22 used Shek's urethra mobility profile and found similar results. The similar thread from all these analyses was that most of the mobility that was observed in SUI was focused on the middle of the urethra.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Ultrasound allows for the measurement of anatomical changes, such as bladder neck mobility or segmental urethral mobility, with high reliability and repeatability (20) . Real-time anatomical change in the lower urinary tract is important for understanding the etiology of SUI, as urethral hypermobility has been implicated as the main mechanism underlying SUI (21) . The study showed a relationship between bladder neck hypermobility and SUI in patients after vaginal delivery, forceps delivery, elective cesarean section and full dilation cesarean section, with a statistical significance level of p <0.002.…”
Section: Discussionmentioning
confidence: 99%